Prevalence of Enterotoxin Genes in Aeromonas spp. Isolated From Children with Diarrhea, Healthy Controls, and the Environment - Albert, M. John (American Society for Microbiology, 2000)
Aeromonads are causative agents of a number of human infections. Even though aeromonads have been isolated from patients suffering from diarrhea, their etiological role in gastroenteritis is unclear. In spite of a number of virulence factors produced by Aeromonas species, their association with diarrhea has not been clearly linked. Recently, we have characterized a heat-labile cytotonic enterotoxin (Alt), a heat-stable cytotonic enterotoxin (Ast), and a cytotoxic enterotoxin (Act) from a diarrheal isolate of Aeromonas hydrophila. Alt and Ast are novel enterotoxins which are not related to cholera toxin; Act is aerolysin related and has hemolytic, cytotoxic, and enterotoxic activities. We studied the distribution of the alt, ast, and act enterotoxin genes in 115 of 125 aeromonads isolated from 1,735 children with diarrhea, in all 27 aeromonads isolated from 830 control children (P = 7 × 10(−4) for comparison of rates of isolation of aeromonads from cases versus those from controls), and in 120 randomly selected aeromonads from different components of surface water in Bangladesh. Aeromonas isolates which were positive only for the presence of the alt gene had similar distributions in the three sources; the number of isolates positive only for the presence of the ast gene was significantly higher for the environmental samples than for samples from diarrheal children; and isolates positive only for the presence of the act gene were not found in any of the three sources. Importantly, the number of isolates positive for both the alt and ast genes was significantly higher for diarrheal children than for control children and the environment. Thus, this is the first study to indicate that the products of both the alt and ast genes may synergistically act to induce severe diarrhea. In 26 patients, Aeromonas spp. were isolated as the sole enteropathogen. Analysis of clinical data from 11 of these patients suggested that isolates positive for both the alt and ast genes were associated with watery diarrhea but that isolates positive only for the alt gene were associated with loose stools. Most of the isolates from the three sources could be classified into seven phenospecies and eight hybridization groups. For the first time, Aeromonas eucrenophila was isolated from two children, one with diarrhea and another without diarrhea.